Generational Differences in the Orientation of Time in Cantonese Speakers as a Function of Changes in the Direction of Chinese Writing - de Sousa, Hilário (Frontiers in Psychology, 2012)
It has long been argued that spatial aspects of language influence people’s conception of time. However, what spatial aspect of language is the most influential in this regard? To test this, two experiments were conducted in Hong Kong and Macau with literate Cantonese speakers. The results suggest that the crucial factor in literate Cantonese people’s spatial conceptualization of time is their experience with writing and reading Chinese script. In Hong Kong and Macau, Chinese script is written either in the traditional vertical orientation, which is still used, or the newer horizontal orientation, which is more common these days. Before the 1950s, the dominant horizontal direction was right-to-left. However, by the 1970s, the dominant horizontal direction had become left-to-right. In both experiments, the older participants predominately demonstrated time in a right-to-left direction, whereas younger participants predominately demonstrated time in a left-to-right direction, consistent with the horizontal direction that was prevalent when they first became literate.